Provincial entrepreneurs in Philippine crafts - Rutten, Rosanne (Philippine Studies, 1992)
Throughout the Philippines, the commercial middle class is gradually expanding on the level of provincial capital, municipal town, and village. The entrepreneurs whom form his class take part in the continuing commercialization of the rural and urban economies, and profit from it. They mostly handle the upward trade of the upward trade of agriculture produce and the downward trade of agriculture inputs and factory-made consumer goods (e.g. Dannhaeuser 1983; Fegan 1989; Wolters 1989). They brokers between city and countryside, and the profitable thanks to their city-countryside links.